(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Experiments were conducted in the cotton field where developments are introduced by the farm "Qasim-karvon", Kuva district, Fergana region. All agricultural activities carried out in the experimental field, including land preparation, planting seeds, harvesting cotton, installing new water-saving irrigation equipment for irrigation, fertilizing, processing between cotton rows, chilpish, control of cotton pests, defoliation and harvesting were carried out.